2020
DOI: 10.2147/dddt.s271191
|View full text |Cite
|
Sign up to set email alerts
|

<p>iTRAQ-Based Quantitative Proteomic Analysis of Intestines in Murine Polymicrobial Sepsis with Hydrogen Gas Treatment</p>

Abstract: Objective Sepsis-associated intestinal injury has a higher morbidity and mortality in patients with sepsis, but there is still no effective treatment. Our research team has proven that inhaling 2% hydrogen gas (H 2 ) can effectively improve sepsis and related organ damage, but the specific molecular mechanism of its role is not clear. In this study, isobaric tags for relative and absolute quantitation (iTRAQ)-based quantitative proteomics analysis was used for studying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 50 publications
1
10
1
Order By: Relevance
“…A variety of trace elements needed by the human body, such as vitamin B and cobalamin, must be absorbed through the intestine, and the absorption of cobalamin needs to be completed by binding proteins [ 39 ]. The protein digestion and absorption signaling pathway is mainly involved in the effective digestion and absorption of intestinal protein and fat [ 40 ]. Studies have shown that the effective digestion and absorption of proteins may be beneficial to cell metabolism, and high-quality cell status can help maintain immunity and functional stability in the body [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of trace elements needed by the human body, such as vitamin B and cobalamin, must be absorbed through the intestine, and the absorption of cobalamin needs to be completed by binding proteins [ 39 ]. The protein digestion and absorption signaling pathway is mainly involved in the effective digestion and absorption of intestinal protein and fat [ 40 ]. Studies have shown that the effective digestion and absorption of proteins may be beneficial to cell metabolism, and high-quality cell status can help maintain immunity and functional stability in the body [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 2%–5% of genes in the human genome encode protein kinases and phosphatases 11 . Previously, our studies demonstrated the differences in protein levels in lung tissues and intestinal tissues from septic animals and those from normal animals 12,13 …”
Section: Introductionmentioning
confidence: 66%
“…In ARDS, the common intrapulmonary and extrapulmonary causes are pneumonia and sepsis, respectively (107-109). It has been shown that 2% hydrogen can effectively ameliorate multiple organ damage and increase the survival rate of sepsis mice (110)(111)(112). Bian et al ( 81) identified differentially expressed proteins, and then elucidated the molecular mechanism of H 2 in treating acute lung injury in sepsis using iTRAQ-based quantitative proteomics analysis.…”
Section: Lung Proteomicsmentioning
confidence: 99%
“…In ARDS, the common intrapulmonary and extrapulmonary causes are pneumonia and sepsis, respectively ( 107 – 109 ). It has been shown that 2% hydrogen can effectively ameliorate multiple organ damage and increase the survival rate of sepsis mice ( 110 112 ). Bian et al.…”
Section: Proteomics In Basic Researchmentioning
confidence: 99%